Afzal Iqbal, The Prophet’s Diplomacy/The Art of Negotiation as Conceived and Developed by the Prophet of Islam, Cape Cod, Massachusetts Claude Stark & Co., 1975, xxxiii + 142 pp. - Chuaqui, Rubén (Estudios de Asia y África, 1988)
-